PERAN ORANG TUA DALAM PENGUATAN KEMAMPUAN SOSIALISASI PADA ANAK USIA 5-6 TAHUN - Sarinah Sarinah; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to describe the role of people in strengthening the socialization skills of children aged 5-6 years in Mengkalang Jambu Village, Kubu Raya Regency. This study uses a qualitative research method with a case study approach, the data collection techniques used are observation, interviews, and documentation. Data collection tools in the form of observation guides, interview guides and documentation. Data analysis was carried out through the stages of data reduction, data display, and verification and drawing conclusions. The validity of the data was tested using source triangulation and technical triangulation.The results of this study indicate that, (1) providing opportunities for children is a method used by parents in strengthening socialization skills in children in Mengkalang Jambu Village, Kubu Raya Regency but still under parental supervision, (2) spending time with children is a way of what parents do in strengthening socialization skills for children in Mengkalang Jambu Village, Kubu Raya Regency, by being invited to communicate, giving understanding and advice, and taking walks, (3) giving motivation is a method used by parents in strengthening socialization skills on children in Mengkalang Jambu Village, Kubu Raya Regency, by giving views to children, giving children social activities and giving gifts for children, (4) guiding children is a method used by parents in strengthening socialization skills in children in Mengkalang Jambu Village, Kubu Regency Raya, by directing children, teaches children to behave well, choose good friends for children so that children can imitate good things.Keywords: Parental Role, Reinforcement, Children's Socialization Ability